Single-Mode Vertical-Cavity Surface-Emitting Laser Array With High Power and Narrow Far-Field Divergence Angle - Jin-Wei Shi; Kai-Lun Chi; Jin-Hao Chang; Zhi-Rui Wei; Jia-Wei Jiang; Ying-Jay Yang (IEEE Photonics Journal)
We demonstrate novel structures of an 850-nm vertical-cavity surface-emitting laser (VCSEL) array for high output power, single-lobe far-field pattern, and narrow divergence angle. By using the Zn-diffusion process with proper sizes of oxide-current-confined and Zn-diffusion apertures, each unit of VCSEL in the demonstrated array is highly single-mode (side-mode suppression ratio <tex Notation="TeX">$>$</tex> 30 dB) with a narrow far-field divergence angle <tex Notation="TeX">$(9^{°}$</tex> – <tex Notation="TeX">$10^{°})$</tex> and high maximum single-mode output power ( <tex Notation="TeX">$\sim$</tex> 6.3 mW). Due to the high uniformity of single-mode performance of each VCSEL unit, the 6 <tex Notation="TeX">$×$</tex> 6 array exhibits an excellent lasing phenomenon, which includes single-lobe far-field pattern, weak in-phase coupling, narrowing of divergence angle (from 9 <tex Notation="TeX">$^{°}$</tex> to 4 <tex Notation="TeX">$^{°}$</tex> ), and output power as high as around 104 mW. Furthermore, by measuring the bias-dependent output optical spectra in different positions of our array, the high similarity of these spectra indicates the excellent uniformity of our fabrication process for single-mode VCSEL.